The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/biom12020332
|View full text |Cite
|
Sign up to set email alerts
|

Network Approaches to Study Endogenous RNA Competition and Its Impact on Tissue-Specific microRNA Functions

Abstract: microRNAs are small non-coding RNAs that play a key role in regulating gene expression. These molecules exert their function through sequence complementarity with microRNA responsive elements and are typically located in the 3′ untranslated region of mRNAs, negatively regulating expression. Even though the relevant role of miRNA-dependent regulation is broadly recognized, the principles governing their ability to lead to specific functional outcomes in distinct cell types are still not well understood. In rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
(88 reference statements)
1
7
0
Order By: Relevance
“…So called miRNA sponge activity is the most commonly described circRNA mechanism of action. This mechanism supports the endogenous RNA hypothesis, whereby specific RNA transcripts, such as circRNAs, can affect the abundance of other RNA molecules by limiting the availability of a common miRNA 54 . In other words, circRNAs inhibit miRNAs to positively regulate the expression of miRNA target genes 16 .…”
Section: Circular Rna Functionssupporting
confidence: 77%
“…So called miRNA sponge activity is the most commonly described circRNA mechanism of action. This mechanism supports the endogenous RNA hypothesis, whereby specific RNA transcripts, such as circRNAs, can affect the abundance of other RNA molecules by limiting the availability of a common miRNA 54 . In other words, circRNAs inhibit miRNAs to positively regulate the expression of miRNA target genes 16 .…”
Section: Circular Rna Functionssupporting
confidence: 77%
“…miR‐129‐5p overexpression (oe) shelters from LPS‐induced podocyte apoptosis, inflammatory response, and acute kidney injury in in vivo and in vitro models of sepsis 13 . Moreover, lncRNAs that function as competitive endogenous RNAs (ceRNAs) can exert regulatory interactions on miRNAs 14 . It is identified and demonstrated that miR‐129‐5p can directly regulate MALAT1 and miR‐129‐5p mimics have the ability to restrain the development of colon cancer cells 15 .…”
Section: Introductionmentioning
confidence: 99%
“…13 Moreover, lncRNAs that function as competitive endogenous RNAs (ceRNAs) can exert regulatory interactions on miRNAs. 14 It is identified and demonstrated that miR-129-5p can directly regulate MA-LAT1 and miR-129-5p mimics have the ability to restrain the development of colon cancer cells. 15 LncRNA MALAT1 might play an important role in sustaining the potential osteoblast differentiation of bone mesenchymal stem cells through sponging miR-129-5p.…”
Section: Introductionmentioning
confidence: 99%
“…However, simplistic approaches do not have the capacity to understand the intricated regulation mechanisms among these ncRNAs. Computational methods are crucial for integrating data as complex as the ncRNA interaction networks, whose crosstalk defines gene expression under determinate conditions (Marques and Gama-Carvalho, 2022). In this study, we obtained the ceRNA network and 22 lncRNA/miRNA/mRNA axes, which potentially control the response of astrocytes against high PA concentrations by mixing transcriptomic data and an in silico approach.…”
Section: Discussionmentioning
confidence: 99%